Visual Outcomes of Pan-retinal Photocoagulation in Diabetic Retinopathy at One-year Follow-up and Associated Risk Factors - Rema Mohan; Sujatha Purushothaman; Pradeepa Rajendra (Indian Journal of Ophthalmology, 2005)
Purpose: To assess the visual outcomes at one-year follow-up after pan-retinal photocoagulation (PRP) in type 2 diabetes mellitus subjects with proliferative diabetic retinopathy (PDR) and associated risk factors. Materials and Methods: A retrospective study, using data from medical records of 5000 Type 2 diabetic patients who underwent a retinal examination between 1995 and 1999 at a diabetic centre. Ocular, clinical and biochemical parameters were assessed at baseline and at one-year follow-up after PRP. Diabetic retinopathy (DR) was documented by colour photography and PRP was performed according to the ETDRS criteria. Results : PRP was done in 413 eyes, of which 261 eyes of 160 subjects were eligible for the study. One hundred and forty eyes (73%) of 191 eyes with good visual acuity (6/9) at baseline maintained the same vision at one-year follow-up. Of the 53 eyes with visual acuity of 6/12-6/36 at baseline, 58.5% (31 eyes) maintained same vision and 18.9% (10 eyes) improved their vision at one-year follow-up. Of the 17 eyes with visual acuity £6/60 at baseline, 12 maintained the same vision and the remaining 5 improved their vision. The causes of visual loss included vitreous haemorrhage in 20 subjects (31.7%), progression of cataract in 19 (30%), chronic macular oedema in 15 (23.8%), pre-retinal haemorrhage in the macula in 6 (9.5%) and pre-retinal fibrosis in the macula in 3 (4.7%) subjects. On multiple logistic regression analysis, diastolic blood pressure ( P =0.03), duration of diabetes ( P =0.006), fasting blood glucose ( P =0.02) and nephropathy ( P =0.01) were associated with decreased vision after PRP. Glycated haemoglobin (HbA1c) ( P <0.001), serum creatinine ( P =0.03), HDL cholesterol ( P =0.05), diabetic neuropathy ( P <0.001), hypertension ( P =0.01) and diabetic nephropathy ( P <0.001) showed a significant association with PDR. Conclusion: Visual acuity at baseline, the duration of diabetes and proteinuria played a significant role in determining the post-PRP visual acuity.